The limit theorem for the maximum ot $C$-valued Gaussian random variables - Matsak, I. K. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The well known asymptotic equality for the maximum of real Gaussian random variables is generalized to the case of random variables with the values taken in the space $C$.